(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
According to the importance of the subject of research, and the importance of the surveyed organization as a dynamic sector of the country in general , The research attempts to suggest to service organizations in general reconsidering the currently adopted mechanisms in the redesign of its functions , and in the services provided industry . The data was collected from (98) Director Mangers , head of department and head of division . The research tool is the questionnaire , which included (50) items . The results show Significant Effect & Correlation relationship between the two variables due to their dimensions . These lead to he application of job enrichment technology will increase the organization’s ability to possess efficient human resources capable of providing distinct services . The research provided some recommendations & suggestions .